Plasma‐initiated chemical vapour deposition of organosiloxane thin films: From the growth mechanisms to ultrathin low‐k polymer insulating layers. Issue 7 (8th April 2020) - Abessolo Ondo, Dominique; Leturcq, Renaud; Boscher, Nicolas D.
Abstract: The growth mechanisms of low dielectric constant polymer thin films elaborated from the atmospheric‐pressure plasma‐initiated chemical vapour deposition (AP‐PiCVD) reaction of a cyclic vinyl organosiloxane are experimentally elucidated in this study. The use of ultrashort plasma pulses (ca. 100 ns), as a polymerisation initiator, with long plasma off‐times results in the formation of atomically smooth thin films. The increase of the monomer saturation ratio, P M / P sat, results in an increase in the growth rate and a better retention of the cyclic structure of the monomer, promoting lower dielectric constants. Based on this experimental study, guidelines are provided to determine the optimal process window for the AP‐PiCVD of functional polymer thin films. Abstract : The growth mechanisms of low dielectric constant polymer thin films elaborated from the atmospheric‐pressure plasma‐initiated chemical vapour deposition (AP‐PiCVD) reaction of a cyclic vinyl organosiloxane are elucidated in this study. The use of ultrashort plasma pulses, as a polymerisation initiator, with long plasma off‐times results in the formation of atomically smooth thin films. The increase of the monomer saturation ratio results in an increase in the growth rate and a better retention of the cyclic structure of the monomer, promoting lower dielectric constants. Guidelines are provided to determine the optimal process window for the AP‐PiCVD of functional polymer thin films.